Photoconductivity and Photoluminescence Studies of Some Chemically Deposited Cd(S-Se):CdCl2, Gd Films - K. Deshmukh1, S. Bhushan1, S. Agrawal2* and (Recent Research in Science and Technology, 2010)
Chemical deposition on appropriate substrate involves precipitation followed by condensation. Films of Cd(S-Se) were prepared by the chemical deposition method using sodium seleno sulphate as Se2- ion source. Results of scanning electron microscopic (SEM) & X-ray diffraction (XRD) studies, optical absorption spectra, photoluminescence (PL) emission spectra and photoconductivity (PC) rise & decay are presented for some Cd (S-Se) films, prepared at 60Â°C and room temperature (RT) on glass substrate, in presence of CdCl2 as flux and Gd as impurity. SEM studies show presence of grains, cluster type and leafy structures along with voids which are related to layered growth. XRD studies show prominent diffraction lines of CdS, CdSe along with that of Gd. The values of strain (Îµ), grain size (D) and dislocation density (Î´) are evaluated from XRD studies and the nature of crystallinity of the films are discussed. From the results of optical absorption spectra, the band gaps are determined. The effect of flux, impurities on the saturated photo to dark current ratio Ipc/Idc is observed in the PC rise and decay studies. The maximum value of Ipc/Idc 107 is obtained for the impurity doped films. The high photo sensitization is related to increase in mobility and lifetime of carriers due to photoexcitation. PL is found to be stronger in films prepared at RT. In PL two peaks are observed which are related to transitions between excitonic levels and levels due to Gd.